Distribution of indications and procedures within the framework of centers participating in the WAA apheresis registry. Issue 1 (February 2017) - Stegmayr, B.; Mörtzell Henriksson, M.; Newman, E.; Witt, V.; Derfler, K.; Leitner, G.; Eloot, S.; Dhondt, A.; Deeren, D.; Rock, G.; Ptak, J.; Blaha, M.; et al.
Abstract: The WAA apheresis registry was established in 2003 and an increasing number of centers have since then included their experience and data of their procedures. The registry now contains data of more than 74, 000 apheresis procedures in more than 10, 000 patients. This report shows that the indications for apheresis procedures are changing towards more oncological diagnoses and stem cell collections from patients and donors and less therapeutic apheresis procedures. In centers that continue to register, the total extent of apheresis procedures and patients treated have expanded during the latest years.